Long-run effects of gestation during the Dutch hunger winter famine on labor market and hospitalization outcomes - Robert S. Scholte; Gerard van den Berg; Maarten Lindeboom (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
The Dutch Hunger Winter (1944/45) is the most-studied famine in the literature on long-run effects of malnutrition in utero. Its temporal and spatial dermacations are clear, it was severe, it was anticipated, and nutritional conditions in society were favorable and stable before and after the famine. This is the first study to analyze effects of in utero exposure on labor market outcomes and hospitalization, and the first to use register data covering the full dutch population to examine long-run effects of this famine. We provide results of famine exposure by sub-interval of gestation. We find a significantly negative effect of exposure during the first trimester of gestation on employment outcomes 53 or more years after birth. Hospitalization rates in the years before retirement are higher after middle or late gestational exposure.
Keywords: I10; I12; J01; J10; J13; J24; 330; nutrition; ageing; developmental origins; morbidity; income; health; employment; Mangelernährung; Schwangerschaft; Kriegsfolgen; Alte Menschen; Erwerbsverlauf; Gesundheit; Niederlande